Attitudes of physical education students towards people with disabilities: a pilot study - Anna Leś; Maria Lipko-Kowalska (Studia Periegetica, 2023)
The purpose of the study was to identify differences in attitudes of students of universities of physical education towards people with disabilities taking into account emotional, cognitive, and behavioral factors. The study involved 126 students of tourism and recreation, physical education, and physiotherapy at two physical education universities in Poland. Respondents’ attitudes were measured using the Polish version of the Multidimensional Attitudes Scale Toward Persons with Disabilities (MAS). The mean score on the MAS-PL scale was 98.47 (SD ± 12.15). No statistically significant correlations were found between scores obtained on the behavioral and cognitive subscales. There was a positive correlation between individual subscales (affective, cognitive, behavioral) and between individual subscales and the total score. Sociodemographic factors (sex, age, place of residence, major subject, and year of study) did not significantly differentiate between students’ attitudes towards people with disabilities. Taking into account results of other studies on this topic, it can be concluded that attitudes of physical education students who participated in the study exhibit towards people with disabilities are more negative than those exhibited by students of social sciences and humanities or medical and health sciences majors.